DELAY EFFECT OF MUD LOADING TO THE OPEN PIT DESIGN IN TERMS OF MEETING 2018 – A COAL PRODUCTION TARGET CASE STUDY OF PIT XYZ AT SOUTH KALIMANTAN - Karel Lutan Warda; Bagus Wiyono; Tedy Agung Cahyadi; Sigit Bagus Prabowo (Puslitbang tekMIRA, 2020)
Based on the 2018, there a mining plan, two temporary sumps, namely the ABC and BCD sumps. They located in a mining sequence pattern. These sumps required a mud loading process prior to mining the coal below the sequence. The mud loading process is loaded sequentialy. However, the problem occurs when the mud loading process in the ABC sump is delayed, and resulted only 42% of mud production. Such the delay resulted in hindering the mining sequence pattern which forced changes in plans, designs, and decrease of coal production. These condition led to study the cause, impact, and alternative solution of the delay during mud loading process. The method used in this study includes direct observations and data collection of working conditions, equipment capabilities, material properties, and operation timeline. In this study, the statistical analysis is used to determine the cause and effect of delayed mud loading process. A Minex Software is then used to simulate the alternative of redesign the mining sequence pattern. The study found that the delay in mud loading process is due to the external and internal factors, that result in underproduction of coal only 505,833 tons, and delayed of coal production around 64 days. An alternative that can be conducted is to change the direction progress to the area that has low stripping ratio. Factors that can hinder the progress are need to be considered for anticipating the plan distraction at mid-term-plan.